Au Nanoparticles-Mesoporous TiO2 Thin Films Composites as SERS Sensors: A Systematic Performance Analysis - Zalduendo, María Mercedes (2018)
The combination of plasmonic nanoparticles and mesoporous materials is of much interest in applications such as sensing or catalysis. The production of such hybrid materials can be done in various ways, leading to different architectures. We present a comparative study of the SERS performance of different nanocomposite architectures comprising mesoporous TiO2 thin films and Au nanoparticles (NPs). The selection of TiO2 as mesoporous support material was based on its high chemical and mechanical stability. Au NPs of different sizes and shapes were placed at different locations of the composite and used as a plasmonic material compatible with the synthesis conditions of the mesoporous films, displaying a high chemical stability. Using p-nitrothiophenol as a molecular probe, we evaluated the performance toward surface-enhanced Raman scattering (SERS) sensing, on the basis of minimum acquisition time, spot-to-spot reproducibility, and limit of detection. The obtained results indicate that each platform features different sensing capabilities. While systems comprising Au NPs within the mesopores allow working with low acquisition times and present high signal uniformity, only a detection limit of micromolar was achieved. On the other hand, those systems made of branched Au NPs covered with mesoporous films require low acquisition times and can achieve detection limits as low as 10 pM, but signal uniformity is compromised. We propose that careful comparison of different SERS platforms based on Au NPs and mesoporous thin films will facilitate selecting an appropriate configuration for any desired application.